Pengaruh Reward Dan Kepuasan Terhadap Motivasi Karyawan PT PLN (Persero) - Sayyidati Hilda Rachma Kamila; Nuruni Ika Kusuma W (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
Employees are human resources who have a very important role for the success of a company. Giving awards for employee welfare and satisfaction should be given more attention because this can improve employee performance. This is done to ensure that the company's goals that have been previously set can be achieved immediately. The purpose of compiling this research is to find, explain, and analyze the effect of reward and satisfaction on employee motivation at PT PLN (Persero).